2018
DOI: 10.1109/jbhi.2017.2679904
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Extracted From Arterial Pulse Waves as Markers of Atherosclerotic Changes: Performance and Repeatability

Abstract: Arterial diseases are significant and increasing cause of mortality and morbidity. In this study, we analyze and compare the discrimination capability of different arterial pulse wave (PW) based indices, both earlier proposed and novel ones, for describing the vascular health. The repeatability of the indices is also evaluated. Both volume PWs and dynamic pressure PWs are recorded by using photoplethysmographic and electromechanical film (EMFi) sensors connected to a wireless body sensor network. The study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…The stiffening of the arteries increases the pulse wave velocity which makes the heart-beat induced wave and first reflected wave more and more overlapping, causing delayed temporal location of the peak value compared with the healthy arteries having more distinct waves. Differences in other upper limb PWderived features, such as augmentation index and reflection index, between healthy controls and atherosclerotic patients have also been observed in an earlier study [19].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The stiffening of the arteries increases the pulse wave velocity which makes the heart-beat induced wave and first reflected wave more and more overlapping, causing delayed temporal location of the peak value compared with the healthy arteries having more distinct waves. Differences in other upper limb PWderived features, such as augmentation index and reflection index, between healthy controls and atherosclerotic patients have also been observed in an earlier study [19].…”
Section: Discussionsupporting
confidence: 68%
“…In the case of non-treated lower limb or upper limb, no consistent changes were observed in the PRT. Based on the present and previous studies, lower limb PW-derived features [8], [9], [12], [16], [19] could add to diagnostics especially in patients presenting with stenoses and mediasclerotic changes of the lower limb arteries. Despite the promising results, further studies with higher sample sizes should confirm and validate the results.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Especially the piezoelectric polymer poly(vinylidenefluoride-co-trifluoroethylene) (P(VDF-TrFE)) has high potential for meeting the aforementioned requirements due to its solution processability, which enables affordable fabrication with additive printing methods, and ability to form thin films for unobtrusive user-experience [9][10] [11]. In this contribution, we study the accuracy and reliability of additively fabricated piezoelectric P(VDF-TrFE) PW sensor signal quality by comparing it to a PW signal obtained concurrently with a reference sensor made of electromechanical film (EMFi) electret material, which has been used earlier in several clinical studies for collecting PW data [21] [22]. Furthermore, 22 test subjects are examined which enables statistical comparison between the proposed P(VDF-TrFE) sensor and the reference sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Systolic toe pressures or toe-to-brachial pressure index (TBI) have also been suggested as an alternative to ABI especially to diabetic patients, but also they have problems with the reliability [6]. Many studies have suggested pulse wave (PW) measurement and analysis for finding vascular abnormalities or abnormal vascular aging [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%